2015
DOI: 10.1242/jcs.165563
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of compositionally and functionally distinct actin filaments

Abstract: The actin filament is astonishingly well conserved across a diverse set of eukaryotic species. It has essentially remained unchanged in the billion years that separate yeast, Arabidopsis and man. In contrast, bacterial actin-like proteins have diverged to the extreme, and many of them are not readily identified from sequence-based homology searches. Here, we present phylogenetic analyses that point to an evolutionary drive to diversify actin filament composition across kingdoms. Bacteria use a one-filament-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
204
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 257 publications
(206 citation statements)
references
References 99 publications
0
204
0
2
Order By: Relevance
“…By contrast, while the Crenarchaeota do not have an FtsZ equivalent, the crenarchaeotal protein crenactin, is related to eukaryotic actin or 'actin-related proteins' and is absent from Euryarchaeota [59]. Actins are structural proteins, often having such diverse functions as providing cell structural support and, in animals, facilitating muscle contraction, for instance [62]. Most recently, it has been shown that a newly discovered group of Archaebacteria-the 'Lokiarchaeota'-possess an actin variant that is the most closely related prokaryotic actin to eukaryotic actins.…”
Section: What Is the Problem With Trees In Prokaryotic Evolution?mentioning
confidence: 99%
“…By contrast, while the Crenarchaeota do not have an FtsZ equivalent, the crenarchaeotal protein crenactin, is related to eukaryotic actin or 'actin-related proteins' and is absent from Euryarchaeota [59]. Actins are structural proteins, often having such diverse functions as providing cell structural support and, in animals, facilitating muscle contraction, for instance [62]. Most recently, it has been shown that a newly discovered group of Archaebacteria-the 'Lokiarchaeota'-possess an actin variant that is the most closely related prokaryotic actin to eukaryotic actins.…”
Section: What Is the Problem With Trees In Prokaryotic Evolution?mentioning
confidence: 99%
“…Eukaryotic cells have a highly ordered and dynamic actin architecture that is accurately and directly regulated by numerous actin binding proteins (ABPs) with different functions (Staiger, 2000;Staiger and Blanchoin, 2006;Fu, 2015). Thus, it has been proposed that the evolution of actin was accompanied by the formation of particular ABPs Gunning et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…S11). The ATP binding site, which is preserved between all actin-like proteins, acts as an ATP hydrolysis and phosphate release controlled conformational switch that is activated by polymerization (21). The ATP switch acts as a timing mechanism to coordinate polymerization and depolymerization (Fig.…”
Section: Significancementioning
confidence: 99%